Advances in Human Factors and Ergonomics in Healthcare and Medical Devices Proceedings of the AHFE 2018 International Conference on Human Factors and Ergonomics in Healthcare and Medical Devices, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Lightner, Nancy J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book shows how human factors and ergonomic principles have been transforming healthcare. It reports on the design of systems and devices to improve quality, safety, efficiency, and effectiveness in patient care, and discusses findings related to improving organizational outcomes in a healthcare setting, as well as approaches for analyzing and modeling those work aspects that are unique to healthcare. Based on the AHFE 2018 International Conference on Human Factors and Ergonomics in Healthcare and Medical Devices, held on July 21-25, 2018, in Orlando, Florida, USA, the book highlights the physical, cognitive and organizational aspects of human factors and ergonomic applications, presenting various perspectives, including those of clinicians, patients, health organizations, and insurance providers. The book is intended as a timely reference guide for researchers involved in the design of medical systems, healthcare professionals managing healthcare settings, as well as healthcarecounselors and international health organizations.
Using design to connect patients, providers, and researchers: A cognitive assessment and monitoring platform for integrative research (CAMPFIRE) -- Soft-brush: A novel tendon driven tactile stimulator for affective touch in children with autism -- The development of an innovative corneal biopsy tool: A usability comparison of four ergonomic handle prototypes -- A cryotherapeutic device for preventing nail toxicity during chemotherapy: Comparison of three cooling strategies -- The feasibility of ontological description of medical device connectivity for laparoscopic surgery -- Smart skin flap postsurgical pre-warning mobile app design -- Delineation of hemorrhagic mass from CT volume -- Factors building commitment of healthcare workers -- Emory healthcare's safe patient handling program -- Human factors for aging consumers -- Improving mobile interfaces for the elderly.
Keywords: Computational intelligence; Engineering design; Occupational health services; Medical informatics; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Engineering Design; Occupational Health; Health Informatics; User Interfaces and Human Computer Interaction